2015
DOI: 10.1504/ijgw.2015.067748
|View full text |Cite
|
Sign up to set email alerts
|

Performance and emission characteristics of CI engine, fuelled with diesel and oxygenated fuel blends

Abstract: Vegetable oils are a potential alternative towards partial or total substitution of diesel fuels. In this study, we used ethanol as the solvent, and a bio fuel enhancer as additive to explore the possible use of higher percentages of biodiesel in an unmodified diesel engine. Biodiesel was produced from cashew nut shell liquid (CNSL) by pyrolysis process. A mixture containing 80% (by volume) of Number 2 diesel fuel and 20% (by volume) of biodiesel is called here as B20. The effect of 10% ethanol, (by volume) bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Fossil diesel has a greater air -fuel ratio than methyl ester (Ramesh et al 2008). A richer air-fuel combination is required at greater output power, as evidenced by the fact that all studied biodiesel mixtures exhibit a decline in the air-fuel ratio (Elango and Senthilkumar 2011;Pushparaj et al 2015;Qenawy et al 2024). Compared to crude diesel, methyl ester mixtures have lower volumetric efficiency because of the higher EGT which heats the entering air (Pushparaj et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossil diesel has a greater air -fuel ratio than methyl ester (Ramesh et al 2008). A richer air-fuel combination is required at greater output power, as evidenced by the fact that all studied biodiesel mixtures exhibit a decline in the air-fuel ratio (Elango and Senthilkumar 2011;Pushparaj et al 2015;Qenawy et al 2024). Compared to crude diesel, methyl ester mixtures have lower volumetric efficiency because of the higher EGT which heats the entering air (Pushparaj et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A richer air-fuel combination is required at greater output power, as evidenced by the fact that all studied biodiesel mixtures exhibit a decline in the air-fuel ratio (Elango and Senthilkumar 2011;Pushparaj et al 2015;Qenawy et al 2024). Compared to crude diesel, methyl ester mixtures have lower volumetric efficiency because of the higher EGT which heats the entering air (Pushparaj et al 2015). The vaporization of pure diesel improves the volumetric efficiency, lowers exhaust gas temperature, and increases air density (Chalatlon et al 2011;Vajja and Murali 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All tested diesel-biodiesel blends show a decreasing air-fuel ratio with increasing engine brake power, manifesting that a richer air- fuel mixture is needed at higher loads. 20,21 Jatropha biodiesel and its mixtures with diesel oil have lower volumetric efficiencies more than crude diesel. This is because the retained exhaust gases have a higher temperature which warm the incoming air and reduce the volumetric efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research of using oxygenated fuel in the engine shows that the diesel blended with oxygenate can significantly reduce the emissions of engine. [10][11][12][13][14] However, with the development of the research, the researchers found that although the oxygenated fuel can improve the in-cylinder combustion process of engine and reduce particulate matter (PM) emissions, the NO x , HC, CO and CO 2 emissions still depend on engine operating condition and the composition of oxygenated fuel. [15][16][17] The combustion in-cylinder of diesel engine is a complex turbulent premixed and diffused combustion process, and the experimental results are affected by many factors.…”
Section: Introductionmentioning
confidence: 99%